Monitoring maturation evolution of ‘Maxi Gala’ apples by a non-destructive fruit analysis method - Magro M.* (2018)
© 2018 International Society for Horticultural Science. All Rights Reserved.The aim of this work was to quantify fruit maturation in ‘Maxi Gala’ apples grafted onto two rootstocks using destructive and non-destructive evaluation methods. The non-destructive method used a portable DA-Meter. The trial was conducted at Vacaria, southern Brazil located 28,44 S and 50,85 W. The fruit samples were picked from two orchards starting six weeks before harvest from January until the second week of February in 2014/15 and 2015/16. The sampling in the orchard was realized in five different points to the two rootstocks M.9 and Marubakaido with M.9 interstem. The samples were collected weekly, consisting of 10 apples in each point and then evaluated destructively (flesh firmness, starch degradation, soluble solids and acidity) and non-destructivly (DA-Meter). For both seasons, the evolution of fruit maturation of ‘Maxi Gala’ was similar between both rootstocks. The DA-Meter produced good correlations with the traditional destructive methods, making it a desirable tool for optimum harvest date determination.